IMPLEMENTASI KEBIJAKAN PENANGANAN TERNAK KORBAN BENCANA ERUPSI MERAPI 2010 (Studi Kasus Di Kabupaten Sleman) - , SUGI WINARSIH; , Dr. Nunuk Dwi Retnandari ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This paper examines the implementation of policies for handling livestock Merapi eruption victims in 2010 in Sleman regency. Issued policies to prevent human casualties due to return back to his home breeders who are in the danger area in order to care for animals that have not been evacuated. Livestock management is a policy which was first performed by the government in disaster management and implementation problems occurred in Sleman. The study was conducted with qualitative methods. Studies show policy goals come true, but there are some problems in the implementation of the policy. The problem is the conflict Head of Dinas Pertanian, Perikanan, dan Kehutanan Sleman with several target groups, do not purchase livestock and livestock didistribusikannya bansos by the Government of Sleman regency, overlapping veterinary services, there is a failure of communication between the team Merapi (Central) with the target group, there was some conflicts of interest and differences occur that disaster management is not optimal. The problems arise because of coordination, communication, differences in interests and management diisaster. Therefore, the recommendations made from these findings is improved coordination by simplifying the process of disbursement of funds and a clear division of labor between Tim Merapi (Central) with District Implementation Team. To improve communication, involving the District Livestock Handling team dealing directly with the public. As for eliminating the differences in interests, people's basic needs must be met in an emergency response. To improve disaster management the need for evacuation of livestock and livestock shelter cage setup on pre-disaster phase and preparation of livestock medicines needed during the emergency response.